Answer:
4x Times the next point will be 11
Step-by-step explanation:
makes most sense mark as brainlst
The students on the right hand side had better overall results
There were less people on the left hand side of the room this affects the average even with the right hand side having two zeros, another thing which the left hand side didn’t have.
Hope I helped
The average rate of change for the function f(x) can be calculated from the following equation
![\frac{f( x_{2})-f( x_{1} )}{ x_{2} - x_{1} }](https://tex.z-dn.net/?f=%20%5Cfrac%7Bf%28%20x_%7B2%7D%29-f%28%20x_%7B1%7D%20%29%7D%7B%20x_%7B2%7D%20-%20x_%7B1%7D%20%7D%20)
By applying the last formula on the given equations
(1) the first function f
from the table f(3π/2) = -2 and f(2π) = 0
∴ The average rate of f =
![\frac{f(2 \pi)-f( \frac{3 \pi}{2} )}{2 \pi - \frac{3 \pi}{2} } = \frac{0-(-2)}{ \frac{\pi}{2} }= \frac{2}{ \frac{\pi}{2} } = \frac{4}{\pi}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bf%282%20%5Cpi%29-f%28%20%5Cfrac%7B3%20%5Cpi%7D%7B2%7D%20%29%7D%7B2%20%5Cpi%20-%20%20%5Cfrac%7B3%20%5Cpi%7D%7B2%7D%20%7D%20%3D%20%20%5Cfrac%7B0-%28-2%29%7D%7B%20%5Cfrac%7B%5Cpi%7D%7B2%7D%20%7D%3D%20%20%5Cfrac%7B2%7D%7B%20%5Cfrac%7B%5Cpi%7D%7B2%7D%20%7D%20%20%3D%20%20%5Cfrac%7B4%7D%7B%5Cpi%7D%20)
(2) the second function g(x)
from the graph g(3π/2) = -2 and g(2π) = 0
∴ The average rate of g =
![\frac{g(2 \pi)-g( \frac{3 \pi}{2} )}{2 \pi - \frac{3 \pi}{2} } = \frac{0-(-2)}{ \frac{\pi}{2} }= \frac{2}{ \frac{\pi}{2} } = \frac{4}{\pi}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bg%282%20%5Cpi%29-g%28%20%5Cfrac%7B3%20%5Cpi%7D%7B2%7D%20%29%7D%7B2%20%0A%5Cpi%20-%20%20%5Cfrac%7B3%20%5Cpi%7D%7B2%7D%20%7D%20%3D%20%20%5Cfrac%7B0-%28-2%29%7D%7B%20%5Cfrac%7B%5Cpi%7D%7B2%7D%20%7D%3D%20%20%5Cfrac%7B2%7D%7B%20%0A%5Cfrac%7B%5Cpi%7D%7B2%7D%20%7D%20%20%3D%20%20%5Cfrac%7B4%7D%7B%5Cpi%7D%20)
(3) the third function h(x) = 6 sin x +1
∴ h(3π/2) = 6 sin (3π/2) + 1 = 6 *(-1) + 1 = -5
h(2π) = 6 sin (2π) + 1 = 6 * 0 + 1 = 1
∴ The average rate of h =
By comparing the results, The <span>function which has the greatest rate of change is h(x)
</span>
So, the correct answer is option <span>
C) h(x)</span>
Answer: Many
Step-by-step explanation: